The influence of self-mastery and communal-mastery on building a model of resiliency - Magno, Carlo (Philippine Journal of Counseling Psychology, 2008)
The study investigated the influence of self-mastery and communal mastery on resiliency using Structural Equations Modeling (SEM). Self-mastery is composed of measures of self-esteem, self-efficacy, self-concept, and spirituality, while communal mastery is composed of social support, and attachment. Resiliency was measured with the dimensions insight, independence, creativity, humor, initiative, and relationships. A total of 379 college students from different colleges and universities answered seven measures. The relationships among the components of self-mastery and communal mastery with resiliency indicate coefficients that are significantly different from zero, p<.05. The measurement model indicates that all manifests of self-mastery have significant parameter estimates except for self-concept, for communal-mastery both attachment and social support are significant, and for resiliency, initiative was not significant. it was found that both self-mastery and communal mastery have significant paths towards resiliency. The study concludes that internal resources and interaction with the environment help an individual become resilient.